The Impact of Social Media Marketing Activities on Purchase Intention - Alnaser, Firas; Alghizzawi, Mahmoud; Abualfalayeh, Ghaith; Omeish, Fandi; Alharthi, Sager; Al Koni, Saed R. (International Review of Management and Marketing, 2024)
This study seeks to investigate the marketing activities available through social media platforms that are reflected in the purchase intention of consumers in general. Further, it explores the joint mediation effect of both perceived value (PV) and social brand engagement (SBE) on SMM-PI connection. A convenience sample strategy was employed to gather data from 338 cosmetic product customers in Palestine through a structured online questionnaire survey. Subsequently, the data underwent examination using intelligent (PLS-SEM) analysis. According to the results of the study, there is a positive relationship between marketing activities through social media platforms on consumer’s beneficial impact on brand perception (PV), consumer engagement (SBE), and purchase intention (PI). Moreover, PV and SBE exert substantial direct beneficial impacts on PI. As for the intermediate effects, they were all effective, and the mediation impact of PV (Perceived Value) and SBE (Social Bonding Experiences) on the relation between SMM and PI is partially complimentary.